COMPARATIVE ANALYSIS OF THE ROLE OF BK IN CHILD FRIENDLY SCHOOLS FOR STUDENTS OF STATE 38 SMP MEDAN AND SINAR HUSNI SMP MEDAN - Hasanah, Anisa (BRIGHT VISION Journal of Language and Education, 2023)
A counseling guidance teacher is a teacher whose job is to provide scientific and professional psychological and humanitarian assistance so that a counseling guidance teacher must try to create good communication with students in facing life's problems and challenges. The role of the guidance and counseling teacher is very influential in achieving independence and developing the character of students as well as developing the potential possessed by students. This research aims to find out whether there is a significant difference between the role of guidance and counseling in child-friendly schools for students at SMP Negeri 38 Medan and SMP Sinar Husni Medan.This research uses a quantitative approach with comparative descriptive methods. The research population was students from SMP Negeri 38 Medan and SMP Sinar Husni Medan. The sampling technique is purposive sampling technique. The instrument used is the rating scale model. The first and second research objectives were analyzed using percentage techniques. Next, the third objective was analyzed using the t test.The findings of this research: (1) according to the student's perspective on the role of guidance and counseling at SMP Negeri 38 Medan, students on average are in the very high category, (2) according to the student's perspective on the role of guidance and counseling at SMP Sinar Husni Medan, students on average is in the medium category, and (3) There is a significant difference between students' perspectives on the role of guidance and counseling in friendly schools and conventional schools.